DIGITALISASI ARSIP KARTOGRAFI DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA YOGYAKARTA - , SONIYA EVA NATALIA N ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report discusses the Cartographic archives digitalization in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta (The Library and Regional Archives of Yogyakarta). Digitizing is the process of creating an electronic files of conventional archive which aims to protect it. Fieldwork Practice is intended as a space to directly determine the process of cartographic archive. The problems are